First record of the genus Mimonemophas Breuning (Coleoptera: Cerambycidae: Lamiinae: Monochamini) from China with description of a new species - Xie, Guanglin; Huang, Jianghua; Wang, Wenkai; Xiang, Lanbin (Zootaxa, 2015)
The little known genus Mimonemophas was erected by Breuning (1961) with M. quadrifasciatus Breuning as the type species, which was described based on a single male specimen from Vietnam. The genus Mimonemophas is similar to Anoplophora Hope in appearance but different from it by elytra densely clothed with thick bristle-like hairs on non-pubescent region, while in Anoplophora, the elytra glabrous, or pubescent with/without hairs, if the hairs present, commonly soft and thin. Until now, the type species was known only from Mau Son Mountain, Vietnam.